2017
DOI: 10.1097/coc.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

Association of Graded Folic Acid Supplementation and Total Plasma Homocysteine Levels With Hematological Toxicity During First-line Treatment of Nonsquamous NSCLC Patients With Pemetrexed-based Chemotherapy

Abstract: Prevalence of elevated tpHcy levels posttreatment as compared with baseline was reduced significantly with FAS. Among ns-NSCLC patients treated with pemetrexed and with FAS of 400 to 1000 μg daily, HTox was not associated with either baseline tpHcy levels or with graded baseline FAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 29 publications
2
45
1
Order By: Relevance
“…ICDs ≥7 days occurred only in approximately 10% of patients and were similar in the 2 arms. However, this was less than our previous observation of approximately 20% in a mixed histology cohort that received several different chemotherapy regimens and in the previous retrospective study on first‐line pemetrexed chemotherapy . Although it was not one of the prespecified outcomes of the current trial, we also observed a trend toward higher objective radiologic responses in the IA.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…ICDs ≥7 days occurred only in approximately 10% of patients and were similar in the 2 arms. However, this was less than our previous observation of approximately 20% in a mixed histology cohort that received several different chemotherapy regimens and in the previous retrospective study on first‐line pemetrexed chemotherapy . Although it was not one of the prespecified outcomes of the current trial, we also observed a trend toward higher objective radiologic responses in the IA.…”
Section: Discussioncontrasting
confidence: 87%
“…The reason for a relatively lower rate of grade 3/4 cytopenias (other than anemia) may be related to the use of a lower dose of cisplatin (65 mg/m 2 is the standard followed at our center) as well as use of the highest permissible FAS (1000 μg daily) . However, the pemetrexed and carboplatin doses are similar to those followed in routine practice globally as well as in other randomized trials.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The Homocysteine Lowering Trialists' Collaboration reported that a maximum reduction of 90% in the plasma homocysteine level can be achieved with 0.4 mg of folic acid per day [14]. Recently, Singh et al [15] reported that hematological toxicity was not associated with plasma homocysteine levels before folate supplementation during first-line treatment of nonsquamous NSCLC patients with pemetrexed-based chemotherapy. Therefore, treatment with 0.5 mg of folic acid is possibly sufficient for most patients.…”
Section: Discussionmentioning
confidence: 97%